2008
DOI: 10.1021/ie071094p
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Reactive Distillation for Fischer−Tropsch Synthesis

Abstract: Fischer-Tropsch synthesis (FTS) is an area that is receiving revived interest worldwide as a technology alternative to produce transportation fuels as well as chemicals from syngas. SASOL and Shell are two of the major players who operate FT reactors on a commercial scale. To have a balance between gasoline and diesel production, one needs to have both the low temperature (LTFT) and high-temperature (HTFT) processes operating in parallel. Heat-removal from the exothermic FT reactions was the main driver in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Removal of methanol and water using membrane reactors [38,39] and by condensation at high pressures [40] or low temperatures [41] has been previously described for gas-phase methanol synthesis. Reactive distillation [42] provides a further possible approach for continuous product removal, particularly in liquid-phase processes, and has been proposed in literature for the methanol synthesis process [43] and for the Fischer-Tropsch process [44] operating at similar conditions. In addition, selective removal of water by adsorption on zeolite molecular sieves has also been suggested in sorption-enhanced methanol [45] and related dimethyl ether [46] synthesis operated in the gas-phase.…”
Section: Figurementioning
confidence: 99%
“…Removal of methanol and water using membrane reactors [38,39] and by condensation at high pressures [40] or low temperatures [41] has been previously described for gas-phase methanol synthesis. Reactive distillation [42] provides a further possible approach for continuous product removal, particularly in liquid-phase processes, and has been proposed in literature for the methanol synthesis process [43] and for the Fischer-Tropsch process [44] operating at similar conditions. In addition, selective removal of water by adsorption on zeolite molecular sieves has also been suggested in sorption-enhanced methanol [45] and related dimethyl ether [46] synthesis operated in the gas-phase.…”
Section: Figurementioning
confidence: 99%
“…Caldwell and van Vuuren were the first to consider the importance of VLE in the FTS modeling . Both Raoult’s Law and more complicated equations of state were adopted to calculate the VLE. Ideal vapor and liquid phase behavior was proven to describe the FTS system with reasonable accuracy. More recently, Jess and co-workers also studied the influence of the condensed phase on the reaction performance in FTS and in particular the phenomenon of pore filling by long-chain hydrocarbons. , They found that industrial-size FTS catalyst pellets operate under severe internal diffusion limitation .…”
Section: Introductionmentioning
confidence: 99%
“…Srinivas et al modified the kinetic parameters for FT reactions in the model proposed by Wang et al to conform to the Aspen Plus power-law formulation. Both Krishna et al and Srinivas et al fixed the chain growth parameter α in their simulations.…”
Section: Fischer–tropsch Kinetic Modelmentioning
confidence: 99%
“…Similar to RD columns, Maretto and Krishna created a simulation model for a multi-stage bubble column for slurry reactor design and optimization, thus reducing the overall backmixing of the slurry phase; however, the separation process was not included. Srinivas et al presented several simulation cases by using an Aspen RadFrac module, with built-in thermodynamic procedures, and gradually increased complexity in the kinetic model and column structure. Moreover, Srinivas et al showed that this RD model predicts performance on par with or better than conventional reactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation